2021
DOI: 10.1038/s41598-021-00871-w
|View full text |Cite
|
Sign up to set email alerts
|

A unique amphiphilic triblock copolymer, nontoxic to human blood and potential supramolecular drug delivery system for dexamethasone

Abstract: The drug delivery system (DDS) often causes toxicity, triggering undesired cellular injuries. Thus, developing supramolecules used as DDS with tunable self-assembly and nontoxic behavior is highly desired. To address this, we aimed to develop a tunable amphiphilic ABA-type triblock copolymer that is nontoxic to human blood cells but also capable of self-assembling, binding and releasing the clinically used drug dexamethasone. We synthesized an ABA-type amphiphilic triblock copolymer (P2L) by incorporating tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…of all the four newly-synthesized compounds 2a-2d were perfectly compliant with the targeted chemical structures. In this model of amphiphilic structure (Figure 3), we can make use of this cocktail or hybrid pharmacophore in many different ways in pharmceutical and medicinal chemistry (Gao et al, 2021;Jubie et al, 2012;Mittal et al, 2021;Mushtaq et al, 2021;Rabie, 2021b). First, pharmacokinetically, if we want to design certain drugs that have all the three main states of gradual polarity (polar, semipolar, and nonpolar) to effectively be distributed and pass through the diverse biological liquids and membranes, hundreds of compounds can be easily synthesized based on this backbone.…”
Section: Resultsmentioning
confidence: 99%
“…of all the four newly-synthesized compounds 2a-2d were perfectly compliant with the targeted chemical structures. In this model of amphiphilic structure (Figure 3), we can make use of this cocktail or hybrid pharmacophore in many different ways in pharmceutical and medicinal chemistry (Gao et al, 2021;Jubie et al, 2012;Mittal et al, 2021;Mushtaq et al, 2021;Rabie, 2021b). First, pharmacokinetically, if we want to design certain drugs that have all the three main states of gradual polarity (polar, semipolar, and nonpolar) to effectively be distributed and pass through the diverse biological liquids and membranes, hundreds of compounds can be easily synthesized based on this backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new treatment strategies are highly desired to prevent bone growth impairment caused by chronic inflammation. Moreover, glucocorticoids (GCs) are also widely used in the management of IBD and several attempts have been made to reduce the toxicity of GCs ( 35 37 ). Interestingly, it has been reported that the combination of the humanin analog HNG with a GC does not interfere with the desired anti-inflammatory effects of the GC ( 12 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, synthetic amphiphilic block copolymers are promising systems. , Amphiphilic block copolymers consist of two or more blocks with various chemical groups. They form highly organized systems, which can be excipients for molecules of drugs.. , Pluronics are among the most widely used block copolymers. A block copolymer Pluronic P123 is a well-known pharmaceutical excipient.…”
Section: Introductionmentioning
confidence: 99%